Žáner — prekliatie a požehnanie slovenského filmu - Juraj Malíček (Literatura i Kultura Popularna)
This study presents key film works of Slovak cinema in the context of its development from the establishment of the independent Slovak Republic to the present day, with an emphasis on the increasingly prevalent inclination of Slovak filmmakers towards so-called genre film. The fact that Slovak cinema seems to have everything — except for an audience — can be considered a long-standing and persistent problem, but it does not explain the entire state of affairs. In fact, among the many films that have been made in Slovakia since 1993 we can also find works that have been extremely successful, at least domestically, and their success was directly caused by the fact they were genre films. At the same time, however, genre is not a guarantee of success, and certainly not of an elevated (not to mention artistic) quality. Therefore, this study will focus primarily on those works that can be considered emblematic to certain genres, but without regard to their success or failure with the audience nor their acceptance by film and art critics.